ẢNH HƯỞNG CỦA CẢM NHẬN RỦI RO ĐẾN THÁI ĐỘ, Ý ĐỊNH VÀ HÀNH VI MUA THỊT LỢN CỦA NGƯỜI TIÊU DÙNG TẠI TP. HỒ CHÍ MINH - Nguyễn, Kim Nam (Trường Đại học Đà Lạt, 2023)
The main aim of this study was to examine the effects of perceived risk on attitudes, intentions and consumers’ behavior regarding pork purchases in Hochiminh City based on the Theory of Reasoned Action in situations of hypothetical food safety risk. Data are from a survey of 240 respondents from Hochiminh City, and a structural equation model approach is used for data analysis. Results indicate that attitudes have a positive effect on intentions, and intentions have a positive effect on behavior. Risk perception has a negative effect on intention and behavior. The study results suggest that when consumers have positive attitudes and perceive lower risks, they have more incentives to purchase.